Tanfīż aṭ-Ṭarīqah (Buzz Group) lī at-Tarqiyyat Natāʾij at-Taʿallum lī aṭ-Ṭullāb fī Māddah al-Lugah al-ʿArabiyyah bī al-Madrasah aṡ-Ṡānawiyyah al-Ḥukūmiyyah: Application of Buzz Group Learning Method to Improve Learning Outcomes in Arabic Language Subjects at MTsN 3 Ngawi - Siti Maharani Hasibuan; Agus Yasin; Azhar Amir Zaen; Sri Wahyuni Utamy (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2024)
Madrasah Tsanawiyah Negeri (MTsN) 3 Ngawi is a public madrasah that implements Arabic language learning for students using Arabic language textbooks from the Ministry of Religious Affairs (KEMENAG). However, there are several issues during the learning process in the teaching and learning program. The teacher still uses the lecture and translation methods, which cause students to become easily bored and less attentive to the teacher's explanations, making the learning process less than optimal and resulting in minimal student learning outcomes. In this study, the researcher used Classroom Action Research (CAR) with four stages: planning, action, observation, and reflection. Therefore, the researcher seeks to solve these issues by implementing the "Buzz Group" learning method, which can improve learning outcomes and student engagement. The results of this study are as follows: 1) the application of the Buzz Group method in Arabic language learning can improve student learning outcomes, as evidenced by the first cycle, where student learning outcomes reached an average score of 88.1 with an achievement rate of 86.66% from 32 students, and in the second cycle, student learning outcomes reached an average score of 93 with an achievement rate of 96.77% from 32 students. 2) Applying the Buzz Group method in Arabic language learning can increase student engagement, as evidenced by 84.58% student engagement in the first cycle and 93.14% in the second cycle from 32 students. Keywords: Buzz Group, Learning method, Learning outcomes